The Bacillus subtilis Conjugative Plasmid pLS20 Encodes Two Ribbon-Helix-Helix Type Auxiliary Relaxosome Proteins That Are Essential for Conjugation - Miguel-Arribas, Andrés; Hao, Jian-An; Luque-Ortega, Juan R.; Ramachandran, Gayetri; Val-Calvo, Jorge; Gago-Córdoba, César; González-Álvarez, Daniel; Abia, David; Alfonso, Carlos; Wu, Ling J.; Meijer, Wilfried J. J. (Frontiers in Microbiology, 2017)
Bacterial conjugation is the process by which a conjugative element (CE) is transferred horizontally from a donor to a recipient cell via a connecting pore. One of the first steps in the conjugation process is the formation of a nucleoprotein complex at the origin of transfer (oriT), where one of the components of the nucleoprotein complex, the relaxase, introduces a site- and strand specific nick to initiate the transfer of a single DNA strand into the recipient cell. In most cases, the nucleoprotein complex involves, besides the relaxase, one or more additional proteins, named auxiliary proteins, which are encoded by the CE and/or the host. The conjugative plasmid pLS20 replicates in the Gram-positive Firmicute bacterium Bacillus subtilis. We have recently identified the relaxase gene and the oriT of pLS20, which are separated by a region of almost 1 kb. Here we show that this region contains two auxiliary genes that we name aux1LS20 and aux2LS20, and which we show are essential for conjugation. Both Aux1LS20 and Aux2LS20 are predicted to contain a Ribbon-Helix-Helix DNA binding motif near their N-terminus. Analyses of the purified proteins show that Aux1LS20 and Aux2LS20 form tetramers and hexamers in solution, respectively, and that they both bind preferentially to oriTLS20, although with different characteristics and specificities. In silico analyses revealed that genes encoding homologs of Aux1LS20 and/or Aux2LS20 are located upstream of almost 400 relaxase genes of the RelLS20 family (MOBL) of relaxases. Thus, Aux1LS20 and Aux2LS20 of pLS20 constitute the founding member of the first two families of auxiliary proteins described for CEs of Gram-positive origin.